Caracterização e eficiência simbiótica em feijão-caupi de estirpes de rizóbio isolados de diferentes regiões de Roraima - Mosqueira, Cátia Aparecida (2014)
The cowpea constitutes one of the legume plants of great importance to the State of Roraima and its cropping can be found in several areas of the region. It is a legume plant which can benefit from the biological fixation through symbiosis with bacteria of the genus Bradyrhizobium. In this way, it was aimed in this work to characterize and evaluate the symbiotic efficiency of strains of rhizobia isolated from Forest and cerrado (savannah-like vegetation) environment in Roraima. The strains were characterized morphologically and grouped together according to the profiles generated; next, they were characterized genetically through the amplification and partial sequencing of gene 16S rRNA. Utilizing the cowpea as a bait plant, an experiment was conducted in a greenhouse for evaluating of the symbiotic efficiency, from which the dry matter of the shoot, number and dry matter of nodules were determined. Of this experiment, eight strains which proved more efficient were tested in field. In the field, two experiments were conducted, one in an area with no previous cropping with cowpea and the other in an area cultivated for two years. Of the Field experiments, at 30 days, dry matter and total-N of the shoot, number and dry mass of nodules were evaluated and at the end of the cycle, grain yield was determined. Of the total of strains characterized, most of them presented slow growth (58%) and neutral reaction (51 %) of the culture medium, characteristics which were consistent with those of the genus Bradyrhizobium. The analysis of the partial sequencing of gene 16SrRNA revealed that the strains obtained of cowpea present a high phenotypic and genotypic diversity, with predominance of strains of the genus Bradyrhizobium ADN to a smaller extent strains with characteristics similar to the genus Rhizobium. The results obtained in the symbiotic efficiency assay showed that 20 strains were efficient, all of them belonging to the genus Bradyrhizobium. Three strains (ERR 24, ERR40 and ERR 510) present good results as regards the symbiotic efficiency for the attributes evaluated under field conditions, presenting satisfactory values concerning the symbiotic efficiency equal or superior to the strains currently recommended and to the nitrogen-containing control, they being recommend as new inoculants.